2022
DOI: 10.1177/00031348211067999
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Early Versus Delayed Completion Thyroidectomy for Malignancy

Abstract: Purpose To determine whether time interval between hemi-thyroidectomy and subsequent completion thyroidectomy impacts outcomes. Methods Retrospective review of 68 patients having completion thyroidectomy from August 2012 to December 2019. Patients were separated into two groups based on the time interval between surgeries: early (≤10 days) or delayed (≥90 days). Results Patients who underwent delayed completion thyroidectomy (n = 17) had significantly higher rates of hypocalcemia and/or hypoparathyroidism ( P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Some authors recommend performing completion surgery either within the first 10 days or after 3 months, reporting increased complication rates in a completion thyroidectomy performed in the intermediate postoperative period (between 10 days and 3 months). However, other studies concluded that timing has no influence on morbidity [36,37].…”
Section: Discussionmentioning
confidence: 98%
“…Some authors recommend performing completion surgery either within the first 10 days or after 3 months, reporting increased complication rates in a completion thyroidectomy performed in the intermediate postoperative period (between 10 days and 3 months). However, other studies concluded that timing has no influence on morbidity [36,37].…”
Section: Discussionmentioning
confidence: 98%
“…2,17,18 One study reported lower rates of hypocalcemia/hypoparathyroidism ( p = 0.03) as well as dysphonia (p = 0.02) in patients undergoing early (≤10 days) as compared to those undergoing delayed (≥90 days) completion thyroidectomy. 35 Another limitation is that our study did not restrict the indications for each surgery type. While different indications (e. g., goiter) may be technically more difficult and increase the risk of complication, the different operations performed reflect the true nature of an endocrine practice.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal time for cT has been suggested by multiple studies and is accordingly reported in the American Thyroid Association guidelines to be performed within 6 months of the operation 2,17,18 . One study reported lower rates of hypocalcemia/hypoparathyroidism ( p = 0.03) as well as dysphonia ( p = 0.02) in patients undergoing early (≤10 days) as compared to those undergoing delayed (≥90 days) completion thyroidectomy 35 . Another limitation is that our study did not restrict the indications for each surgery type.…”
Section: Discussionmentioning
confidence: 99%